求证a+b+c≥3(abc)^1⼀3,a,b,c,为正实数。

2025-02-28 13:59:01
推荐回答(2个)
回答1:

引入正数x、y、z,显然有:(x-y)^2≧0, ∴x^2-2xy+y^2≧0, ∴x^2+y^2≧2xy。
同理,有:x^2+z^2≧2xz、 y^2+z^2≧2yz。

显然还有:(x+y)(x-y)^2≧0, ∴(x^2-y^2)(x-y)≧0,
∴x(x^2-y^2)-y(x^2-y^2)≧0, ∴x^3-xy^2-x^2y+y^3≧0,
∴x^3+y^3≧x^2y+xy^2。
同理,有:x^3+z^3≧x^2z+xz^2、 y^3+z^3≧y^2z+yz^2。
于是:
(x^3+y^3)+(x^3+z^3)+(y^3+z^3)≧(x^2y+xy^2)+(x^2z+xz^2)+(y^2z+yz^2),
∴2(x^3+y^3+z^3)≧(x^2y+yz^2)+(xy^2+xz^2)+(x^2z+y^2z),
∴2(x^3+y^3+z^3)≧y(x^2+z^2)+x(y^2+z^2)+z(x^2+y^2),
∴2(x^3+y^3+z^3)≧y(2xz)+x(2yz)+z(2xy)=6xyz,
∴x^3+y^3+z^3≧3xyz。
令上式中的x^3=a、y^3=b、z^3=c,得:xyz=(abc)^(1/3),
∴a+b+c≧3(abc)^(1/3)。

回答2:

x^3+y^3+z^3-3xyz = (x+y+z)(x^2+y^2+z^2-xy-yz-xz)
2(x^2+y^2+z^2-xy-yz-xz) = (x-y)^2+(y-z)^2+(x-z)^2 >=0
所以x^3+y^3+z^3-3xyz >= 0